Synthesis and photoluminescence properties of co‐polyamides with anthrazoline‐containing units in the main chain. (1st March 2018) - Goikhman, Mikhail Ya.; Valieva, Irina A.; Podeshvo, Irina V.; Gofman, Iosif V.; Smyslov, Ruslan Yu.; Litvinova, Larissa S.; Yakimansky, Alexander V.
Abstract: A series of anthrazoline‐containing monomers are synthesized, and eight co‐polyamides of different chemical structures, containing 1, 9‐anthrazoline fragments in the main chain, are obtained and investigated. Photoluminescent, stress–strain, and thermal properties of these polymers are studied. It is shown that polymers with fragments of 4, 4′‐(pyrido[3, 2‐g]‐quinoline‐2, 8‐diyl)dianiline and 4, 4′‐(10‐methylpyrido[3, 2‐g]quinoline‐2, 8‐diyl)dianiline possess an intense luminescence in the range 550–650 nm. The performed investigations made it possible to determine the effect of substituents of various natures in the anthrazoline cycle and the position of amide group (meta‐ and para‐configurations) on optical, stress‐strain, and thermal properties of copolymers, opening up a prospect for further developments of principles of design of polymers with optimal characteristics.